2019
DOI: 10.2147/ott.s228231
|View full text |Cite
|
Sign up to set email alerts
|

<p>Linc00511 Indicates A Poor Prognosis Of Liver Hepatocellular Carcinoma</p>

Abstract: ObjectiveTo uncover the specific function of linc00511 in the progression of liver hepatocellular carcinoma (LIHC) and the underlying mechanism.Patients and methodsGEPIA dataset containing 9736 LIHC samples and 857 normal samples were downloaded from TCGA. Expression pattern and prognostic potential of linc00511 in LIHC were analyzed. Subsequently, expression level of linc00511 in LIHC tissues collected in our hospital and cell lines were determined by quantitative real-time polymerase chain reaction (qRT-PCR)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 27 publications
1
13
0
Order By: Relevance
“…Previous studies revealed that the ceRNA role of LINC00511 has been observed in the gastric cancer cell growth promotion process (32). It is demonstrated that the invasion and proliferation are also related to the up-regulation of LINC00511 and the poor prognosis of hepatocellular carcinoma Pingan Hu and others, " LINC00511 Indicates a poor prognosis of liver hepatocellular varcinoma (33). Also, the ceRNA role of LINC00511 in the T-cell acute lymphoblastic leukemia (34) and osteosarcoma (35) had been observed.…”
Section: Discussionmentioning
confidence: 98%
“…Previous studies revealed that the ceRNA role of LINC00511 has been observed in the gastric cancer cell growth promotion process (32). It is demonstrated that the invasion and proliferation are also related to the up-regulation of LINC00511 and the poor prognosis of hepatocellular carcinoma Pingan Hu and others, " LINC00511 Indicates a poor prognosis of liver hepatocellular varcinoma (33). Also, the ceRNA role of LINC00511 in the T-cell acute lymphoblastic leukemia (34) and osteosarcoma (35) had been observed.…”
Section: Discussionmentioning
confidence: 98%
“…In HCC, LINC00511 promoted the proliferation, colony formation, migration, and invasion of cancer cells by targeting miR-424 and miR-29c , and regulating the miR-195 / eyes absent homolog 1 axis. [ 14 – 16 ] Jiang et al [ 36 ] also suggested that silencing LINC00511 would suppress the proliferation, migration, and epithelial-mesenchymal transition of lung cancer cells by modulating the PTEN/AKT/FOXO1 axis. Moreover, Li et al [ 37 ] found that overexpression of LINC00511 enhanced the proliferation and invasion of glioma cells through inhibition of miR-124-3p and concomitant upregulation of cyclin D2.…”
Section: Discussionmentioning
confidence: 99%
“…[ 5 7 ] The long intergenic noncoding RNA 00511 ( LINC00511 ) was firstly identified in 2015 by Cabanski et al [ 8 ] Subsequently, several studies reported that abnormal LINC00511 expression was correlated with prognosis in patients with malignancies. Moreover, most studies suggested that LINC00511 could act as an oncogene and its high expression was predictive of poor prognosis in various malignancies, such as cervical cancer (CC), [ 9 , 10 ] ovarian cancer (OC), [ 11 – 13 ] hepatocellular carcinoma (HCC), [ 14 – 16 ] pancreatic cancer, [ 17 ] lung cancer, [ 18 , 19 ] breast cancer, [ 20 – 24 ] renal cancer, [ 25 ] and glioma. [ 26 , 27 ] Nevertheless, some studies also reported that LINC00511 could be a tumor suppressor, with high LINC00511 expression being associated with favorable prognosis of some cancer patients.…”
Section: Introductionmentioning
confidence: 99%
“…Overexpression of lnc-MUC20-9 in bladder cancer cells leads to the reduced viability, colony formation, migration, invasion, and increased apoptosis [8]. LINC00511 is transcribed from chromosome 17q24.3 region, and it is upregulated in tumors such as hepatocellular carcinoma, colorectal cancer, and GC [9][10][11].…”
Section: Introductionmentioning
confidence: 99%